First record of non-native polychaetes Polydora websteri and P. caeca invading cultured and wild populations of mussels and oysters in the Mediterranean - Barbara Mikac; Vasily I. Radashevsky; Eugenio Fossi; Victoria V. Pankova; Marina Antonia Colangelo; Giuseppe Prioli; Marco Abbiati; Federica Costantini (Aquaculture Reports)
Species of Polydora and related genera are well known molluscs’ pests transported by aquaculture activities and invading new locations worldwide. Their correct identification often requires confirmation by molecular data due to the presence of cryptic species. In the present study, using morphological and molecular data, we identified three non-native Polydora species associated with cultured and wild mussel Mytilus galloprovincialis, Pacific oyster Magallana gigas and European oyster Ostrea edulis in the Adriatic Sea (Italy). The tube-dwelling P. cornuta has been recorded from the Mediterranean since 1990 and is currently classified as one of the worst invaders in soft bottom communities in the region. The shell-boring P. caeca and P. websteri are here reported for the first time in the Mediterranean. This occurrence is a cause for concern, as the regular transfer of molluscs between aquaculture facilities within the Mediterranean basin and with European farms outside the basin may contribute to the further spread of the non-native Polydora in this region. The origin and distribution of these species in the Mediterranean should be further studied.